Analisis Korelasi Atribut dengan Keputusan Pembelian Konsumen Jamu Tradisional di Baturaja Kabupaten Ogan Komering Ulu - Endang Lastinawati (KaliAgri Journal, 2025)
Jamu is a health drink inherited from culture and natural resources that is consumed to this day. This study aims to analyze the relationship between herbal medicine attributes and consumer purchasing decisions in Baturaja, Ogan Komering Ulu Regency. The study used a survey method, by taking a sample of 25 herbal medicine consumers incidentally. The results showed that there was a fairly strong correlation between herbal medicine packaging and consumer decisions to purchase herbal medicine, a very strong correlation between efficacy and the decision to purchase herbal medicine, a very weak correlation between herbal medicine taste and the decision to purchase herbal medicine, a very weak correlation between the product's expiration date and the decision to purchase herbal medicine, and a very weak correlation between safety and the decision to purchase herbal medicine. Further research is expected to be conducted, especially related to the causal relationship between consumers consuming herbal medicine, so that it can provide a comprehensive contribution to the preservation of traditional herbal medicine.